Low ficolin-3 levels in early follow-up serum samples are associated with the severity and unfavorable outcome of acute ischemic stroke - Füst, George; Munthe-Fog, Lea; Illes, Zsolt; Széplaki, Gábor; Molnar, Tihamér; Pusch, Gabriella; Hirschberg, Kristóf; Szegedi, Robert; Széplaki, Zoltán; Prohászka, Zoltán; Skjoedt, Mikkel-Ole; Garred, Peter (Journal of neuroinflammation, 2011)
A number of data indicate that the lectin pathway of complement activation contributes to the pathophysiology of ischemic stroke. The lectin pathway may be triggered by the binding of mannose-binding lectin (MBL), ficolin-2 or ficolin-3 to different ligands. Although several papers demonstrated the significance of MBL in ischemic stroke, the role of ficolins has not been examined.
Gesehen am 03.07.2023